Development of humanistic nursing practice guidelines for stroke patients - Li, Min; Ji, Yu-gui; Yang, Zi-qing; Xie, Hong-zhen (Frontiers in Public Health, 2022)
Purpose To construct humanistic nursing practice guidelines suitable for stroke patients. Design This study was a development and validation study of guidelines using multiple methods, including literature review, qualitative research, questionnaire survey, thematic discussion, and Delphi expert consultation. Methods Twenty-five experts from seven provinces and municipalities in China were interviewed over two rounds from December 2020 to February 2021. The first-level index was scored for importance and rationality, while the second-level index was scored for importance and feasibility using a five-point Likert scale. Delphi data was collected via a paper version of the questionnaire. The coefficients of variation and coordination were used to represent the degree of dispersion of expert opinions. Findings In the two rounds of letter consultation, the questionnaire's recovery and effective rates were both 100%, while the opinion submission rates of the two rounds were 84 and 52%, respectively. Moreover, the expert authority coefficient was 0.91, and the coordination coefficients of expert opinions in the first round were as follows: importance of 0.03 and rationality of 0.07 for the first-level index; importance of 0.09 and feasibility of 0.11 for the secondary index. In round two, the coordination coefficients of expert opinions were as follows: importance of 0.04 and rationality of 0.05 for the first-level indicators; importance of 0.12 and feasibility of 0.10 for the secondary index. The results for the secondary index were P < 0.001 for the two rounds. The humanistic nursing practice guidelines for stroke patients that were ultimately formed included five first-level indicators (physiological care, safety care, emotional care, dignity care, and rehabilitation needs) and 46 s-level indicators. Conclusion Our results show that the “Practice Guidelines for Humanistic Nursing for Stroke” established by experts adopts Maslow's hierarchy of needs as its structural framework. It meets people's basic needs and can provide a reference for the construction of a humanistic nursing specialty practice for stroke patients. Clinical relevance Humanistic nursing guidelines for stroke could provide a reference for the construction of humanistic nursing practice in the stroke specialty. Clinical resources Copeptin and long-term risk of recurrent vascular events after transient ischemic attack and ischemic stroke: population-based study https://pubmed.ncbi.nlm.nih.gov/26451023/. Effectiveness and usage of a decision support system to improve stroke prevention in general practice: a cluster randomized controlled trial https://pubmed.ncbi.nlm.nih.gov/28245247/. Guidelines for adult stroke rehabilitation and recovery: a guideline for healthcare professionals from the American Heart Association/American Stroke Association https://pubmed.ncbi.nlm.nih.gov/27145936/.